(untitled) (Swiss Medical Weekly, 2023)
BACKGROUND: Worldwide, almost half of all heart transplantation candidates arrive today at their transplant operation with durable continuous-flow mechanical circulatory support (CF-MCS). This evolution is due to a progressive increase of waiting list time and hence an increased risk of haemodynamic worsening. Longer duration of CF-MCS is associated with a higher risk of device-related complications with potential adverse impact on post-transplant outcome as suggested by recent results from the United Network of Organ Sharing of the United States. METHODS: A 2-centre Swiss heart transplantation programme conducted a retrospective observational study of consecutive patients of theirs who underwent a transplant in the period 2008–2020. The primary aim was to determine whether post-transplant all-cause mortality is different between heart transplant recipients without or with pre-transplant CF-MCS. The secondary outcome was the acute cellular rejection score within the first year post-transplant. RESULTS: The study participants had a median age of 54 years; 38/158 (24%) were females. 53/158 study participants (34%) had pre-transplant CF-MCS with a median treatment duration of 280 days. In heart transplant recipients with pre-transplant CF-MCS, the prevalence of ischaemic cardiomyopathy was higher (51 vs 32%; p = 0.013), the left ventricular ejection fraction was lower (20 vs 25; p = 0.047) and pulmonary vascular resistance was higher (2.3 vs 2.1 Wood Units; p = 0.047). Over the study period, the proportion of heart transplant recipients with pre-transplant CF-MCS and the duration of pre-transplant CF-MCS treatment increased (2008–2014 vs 2015–2020: 22% vs 45%, p = 0.009; increase of treatment days per year: 34.4 ± 11.2 days, p = 0.003; respectively). The primary and secondary outcomes were not different between heart transplant recipients with pre-transplant CF-MCS or direct heart transplantation (log-rank p = 0.515; 0.16 vs 0.14, respectively; p = 0.81). CONCLUSION: This data indicates that the strategy of pre-transplant CF-MCS with subsequent orthotopic heart transplantation provides post-transplant outcomes not different to direct heart transplantation despite the fact that the duration of pre-transplant assist device treatment has progressively increased.